Pathfinder: an online collaboration environment for citizen scientists - Luther, Kurt; Counts, Scott; Stecher, Kristin B.; Hoff, Aaron; Johns, Paul (CHI '09: Proceedings of the 27th international conference on Human factors in computing systems, 2009)
For over a century, citizen scientists have volunteered to collect huge quantities of data for professional scientists to analyze. We designed Pathfinder, an online environment that challenges this traditional division of labor by providing tools for citizen scientists to collaboratively discuss and analyze the data they collect. We evaluated Pathfinder in a sustainability and commuting context using a mixed methods approach in both naturalistic and experimental settings. Our results showed that citizen scientists preferred Pathfinder to a standard wiki and were able to go beyond data collection and engage in deeper discussion and analyses. We also found that citizen scientists require special types of technological support because they generate original research. This paper offers an early example of the mutually beneficial relationship between HCI and citizen science.